Basic income and its applicability in Turkey - Sahin, Senem Cakmak; Kilic, Ibrahim Engin (CAMBRIDGE UNIV PRESS, 2021)
In search of justice in income distribution and easy access to necessities by everyone, basic income (BI) has become one of the main topics of conversation. However, there is no comprehensive study on the cost and effect of BI in Turkey. This study aims to set a theoretical framework for BI, compare different views on the topic, evaluate implementations from the world, and analyze the feasibility of a BI program in Turkey by estimating its costs and distributional consequences using a tax-benefit microsimulation. The results show that, although it improves the income distribution, implementing a basic income scheme financed by income tax would impose a significant burden on the upper half of the income distribution due to widespread poverty and income inequality. In the baseline, individual-based scenario, every individual aged 15 or above is granted a BI equal to the poverty line, while children below age 15 are granted 30 percent of this amount. This plan costs 17.77 percent of the gross domestic product and it is covered by multiplying current income tax by 3.54. Implementation of this plan decreases the poverty rate from 12.43 percent to zero and the Gini index from 0.388 to 0.181.
Keywords: basic income; income distribution; tax-benefit microsimulation; Area Studies; Social Sciences - Other Topics